An Analysis of Identification of Studentsâ€™ Need in Learning English at Marketing Department of SMK Negeri 1 Kolaka - Suryadi, Ray; Hendra (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2021)
This research is aimed to answer the problem of the research â€œWhat are the studentsâ€™ needs in the Marketing Department at SMK Negeri 1 Kolaka in learning English?â€ This research uses a qualitative research design where the data are explained in the description form. The instruments of the research are questionnaires and interview guidelines. The participants of the research are students of the Marketing Department in the second grade in SMK Negeri 1 Kolaka. The result showed the student needs, the first is for the student's necessities who are more likely to learn speaking skills, and also for the material they wanted is online marketing material, which means that they considered their needs in the future when they enter the world of work, another thing that studentsâ€™ needs in their English learning is they need a material that is appropriate to their major so that what they learn in school can be applied when they are working later, while the studentsâ€™ lack is their speaking skill and also vocabulary deficiencies. Where they have no space or place to use their English skills that they have learned and for the desires of students in terms of learning English, students are more likely want to learn English by going outside. And for the learning methods that used by the teacher, students are more likely want to study in pairs or groups with their friends rather than study alone. Besides, students also want the teachers who can become facilitators and guides in the English learning process.